The Effect of Road Conditions on Acacia mangium Timber Hauling Performance - Yuniawati Yuniawati; Sarah Andini (Faculty of Forestry Universitas Gadjah Mada, 2023)
The quality of timber could be affected by timber hauling, primarily when it remained in the forest and became vulnerable to pests and fungi attacks. Additionally, road conditions could also influence the slickness of hauling. Therefore, this study aimed to identify the effect of road conditions on hauling performance, cost, and soil deterioration. This research analyzed four types of road conditions in Acacia mangium plantations in West Java and Banten, including dry, wet, uphill, and downhill roads. The results indicated that the average hauling performance of 6.604 m3km/hour on the uphill road was the least among all road types. The uphill soil road had the highest average hauling cost of 30,685 IDR/m3km and the deepest average rut of 17.503 cm compared to others. These results would provide better information on low-cost and environmentally friendly timber hauling productivity.